2008
DOI: 10.1038/hdy.2008.33
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive responses of independent traits to the same environmental gradient in the intertidal snail Bembicium vittatum

Abstract: The snail Bembicium vittatum occupies a wide range of intertidal habitats in the Houtman Abrolhos Islands, Western Australia. Allozyme variation reflects patterns of connectivity, which are independent of local habitat. In contrast, heritable differences in shell shape among 83 shore sites vary with habitat, indicating local adaptation. Here we examine dimorphisms of colour and spotting of the shell in the same populations, as a test of consistency and complexity of patterns of local adaptation. Within populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Shell polymorphisms in snails are useful models for studying the complexity of adaptation, because likely mechanisms of selection are often clear in terms of selective predation or climatic selection (Jones et al, 1977;Clarke et al, 1978;Cain, 1983;Vermeij, 1993), allowing predictions of responses to changes in habitat or climate. Examples of multiple traits associated with significant environmental gradients include colour and banding in the land snail Cepaea nemoralis (see Jones et al, 1977;Cook, 2005;Ozgo, 2011), colour and shape in the littorine Bembicium vittatum (Johnson and Black, 2008), and shape and molecular markers in Littorina saxatilis (Grahame et al, 2006;Galindo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Shell polymorphisms in snails are useful models for studying the complexity of adaptation, because likely mechanisms of selection are often clear in terms of selective predation or climatic selection (Jones et al, 1977;Clarke et al, 1978;Cain, 1983;Vermeij, 1993), allowing predictions of responses to changes in habitat or climate. Examples of multiple traits associated with significant environmental gradients include colour and banding in the land snail Cepaea nemoralis (see Jones et al, 1977;Cook, 2005;Ozgo, 2011), colour and shape in the littorine Bembicium vittatum (Johnson and Black, 2008), and shape and molecular markers in Littorina saxatilis (Grahame et al, 2006;Galindo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, shell shape is associated with elevational variation in moisture levels, so that bulimulid species with more slender shells (and a smaller shell opening relative to shell size) tend to be found at lower elevations, whereas species that are more conical in shape tend to be found at higher elevations where humidity levels are higher . Shell morphology (especially shape and size) has been associated with adaptation to the environment in other snail taxa (e.g., Goodfriend 1986;Schilthuizen et al 2006;Conde-Padin et al 2007;Johnson and Black 2008;Guerra-Varela et al 2009). Other studies of land snails have also demonstrated that species compete for microhabitat, such that interactions within and between species mediate diversification in ecological and morphological traits (Baur and Baur 1990;Chiba 1996Chiba , 1999Chiba , 2004Lee and Silliman 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, basing model parameters on a study documenting the results of transplants experiments of three gastropods ecomorphs (Johnson and Black 2008), Urdy et al (2010b) reproduced the main aspects of the variation in size, shape, and growth rates within and among populations when bred in their own habitat or transplanted to another ecotype habitat (Fig. 6.4).…”
Section: Urdy Et Al's Model Aka the Growth Vector Modelmentioning
confidence: 96%